Association of Hemorrhoids With Hashimoto's Thyroiditis and Associated Comorbidities: A Nationwide Population-Based Cohort Study - Hsu, Sheng-Pang; Chen, Hsin-Hung; Wang, Tzu-Yuan; Ho, Chun-Wei; Hsieh, Ming-Chia; Yip, Hei-Tung; Kao, Chia-Hung (Frontiers in Endocrinology, 2020)
Background: To evaluate the relationship between hemorrhoids and Hashimoto’s thyroiditis (HT). Methods: Using Taiwan’s Longitudinal Health Insurance Database, we compared the incident risk of HT between the study cohort (comprising patients with hemorrhoids) and the comparison cohort (comprising patients without hemorrhoids). Both cohorts were followed from index date until the date of HT diagnosis, withdrawal from the National Health Insurance program, or the end of 2015. Results: The study cohort and comparison cohort comprised 6,486 patients with hemorrhoids and 25,944 patients without, respectively. The mean follow-up time was approximately 3 years. The incidence rate of HT in the study cohort was 5.37 per 1,000 person-years, which was higher than that of the control cohort (2.46 per 1,000 person-years). The risk of developing HT in the study cohort was 2.06 times (95% confidence interval [CI] =1.02, 4.19) higher than that in the comparison cohort. Conclusion: In our study, patients with hemorrhoids could be at increased risk of HT compared with patients with other comorbidities of HT, such as cardiovascular disease.